Seed reserves partition and light compensation point of mahogany (Swietenia macrophylla King) seedlings growth under low photosynthetic active radiation - José Pires de Lemos Filho; Ricardo Jenner Duarte (Brazilian Archives of Biology and Technology, 1998)
The aim of this study was to verify the dry mass partition of the seed reserves during the initial growth of Swietenia macrophylla seedlings, in the dark, and at low levels of photosynthetically active radiation: 0.125; 3.12 and 52 µ mol.m-2.s-1. After 50 days, the dry mass of the seed reserves did not differ with treatments, but the total dry mass and leaf area were higher in the seedlings under higher light treatment. No difference in root/shoot ratio was observed between treatments, but the leaf area ratio was lower at higher light. Only the seedlings grown at 52 µ mol.m-2.s-1 showed a positive dry mass increase in relation to the mobilized seed reserves. With the values of the net increase of the seedling mass, a linear equation was adjusted in relation to the light levels, permitting to determine 3.76 µ mol.m-2.s-1 as the seedling light compensation point. These results explain the shade tolerance of the S. macrophylla seedlings. O objetivo deste estudo foi verificar a partição da massa seca das reservas das sementes durante o crescimento de plântulas de Sietenia macrophylla , no escuro e sob baixos níveis de radiação fotossintéticamente ativa: 0,125; 3,12 e 52µ mol.m-2.s-1. Após 50 dias a massa seca das reservas das sementes não diferiram com os diferentes tratamentos de luz. Não foi observado diferenças na razão raíz/parte aérea, mas a razão área foliar foi menor no maior nível de luz. Somente as plântulas crescidas a 52 µ mol.m-2.s-1 mostraram um incremento positivo na massa seca em relação às reservas mobilizadas da semente. Uma equação linear foi ajustada entre o incremento líquido de massa seca das plântulas e níveis de luz, permitindo determinar 3,76 µ mol.m-2.s-1 como ponto de compensação de luz das plântulas. Esses resultados explicam a tolerância à sombra das plântulas de S. macrophylla